Improving News Text Writing Skills Using the Picture and Picture Learning Model for Class XI TAB 1 Students at SMKN 5 Surabaya - Dony; Rini Damayanti; Sumara Arisanthi (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to improve the news text writing skills of class This research uses the Classroom Action Research (CAR) method with 4 stages, namely planning, action, observation and reflection. The research results show that the picture and picture learning model by producing products in the form of text using the discovery learning learning method is able to improve the ability to write news texts. This is proven by the increase in grades and writing results from cycle I to cycle II. In cycle I, the lowest value was 55 and the highest is 75 with an average increase of 21%. In cycle II, the lowest score was 80 and the highest was 95 with an average increase of 42%. The conclusion in this research is that using the picture and picture learning model by producing products in the form of text with the discovery learning learning method can improve news text writing skills in class XI TAB 1 SMKN 5 Surabaya.